Decision making application in collaborative emergency response: A new PROMETHEE preference function. (August 2019) - Nassereddine, M.; Azar, A.; Rajabzadeh, A.; Afsar, A.
Abstract: Emergencies or disasters encourage various agencies in a country to cooperate and collaborate to minimize the level of casualties. Hence, the desired overall system performance is influenced not only by the efficiency of each system but also by the synergy between the independent systems, which is critical for emergency response management. This paper presents a multi-criteria decision making (MCDM) approach to evaluate emergency response systems by taking into account the interactions synergy. The study is planned in two major phases, the first uses PROMETHEE method to evaluate emergency response systems. So a new type of preference function is proposed, which is able to overcome the main shortcomings of other preference functions. It helps to extend the range of choices for experts and decision makers. The simplicity and easiness of application are a big bonus of the proposed function. The second phase employs a pairwise comparison of synergy criteria to assess the ratings of systems in coordination and collaboration with each other during the emergency response. Incorporating synergy with MCDM makes more realistic results which helps policy makers to improve the performance of emergency response management. The proposed model is proofed in a real-world case of Lebanon for efficiency and applicability, while the reliability of the proposed function also is investigated through sensitivity analysis. Highlights: We Proposed a new type of preference function. The proposed preference function overcomes main shortcomings of other preference functions. The proposed function helps to extend the range of choices for decision makers. A pairwise comparison of synergy criteria is applied to assess the coordination ratings. A numerical application is presented in Lebanon.